Effects of hyperbaric oxygen (HBO), as pre-conditioning in liver of rats submitted to periodic liver ischemia/reperfusion - Caldeira,Diego Elias da Silva (2013)
PURPOSE: to assess the effect of hyperbaric oxygen (HBO) as pre-conditioning on periodic liver ischemia/reperfusion injury. METHODS: Thirty-six male Wistar rats were divided into 4 groups (SHAM, I/R , HBO-I/R and CONTROL). The surgical technique consisted of total clamping of the hepatic pedicle for 15 min followed by twice repeated reperfusion for 5 min (unclamping). HBO was applied in a collective chamber (simultaneous exposure of 4 rats) directly pressurized with oxygen at 2 ATA for 60 min. Hepatic mitochondrial function was determined using samples of the median lobe obtained after exactly 5 min of reperfusion for the analysis of mitochondrial respiration based on the determination of states 3 and 4, the respiratory control ratio and the transition of mitochondrial permeability (mitochondrial swelling).Data were analyzed by the Mann-Whitney test and the level of significance was set at p < 0.05. RESULTS: There was a statistically significant difference (p< 0.05) in state 3 between the CONTROL and I/R and HBO-I/R groups, in state 4 between the CONTROL and I/R and HBO-I/R groups; in respiratory control ratio (RCR) between the CONTROL and I/R and HBO-I/R groups and between the CONTROL and Sham groups, and in mitochondrial swelling between the CONTROL and I/R and HBO-/R groups and between the Sham and I/R and HBO-I/R groups. CONCLUSION: In this process of periodic ischemia and reperfusion, hyperbaric pre-conditioning did not improve significantly hepatic mitochondrial function.